Ecdysis Triggering Hormone Signaling (ETH/ETHR-A) Is Required for the Larva-Larva Ecdysis in Bactrocera dorsalis (Diptera: Tephritidae) - Shi, Yan; Jiang, Hong-Bo; Gui, Shun-Hua; Liu, Xiao-Qiang; Pei, Yu-Xia; Xu, Li; Smagghe, Guy; Wang, Jin-Jun (Frontiers in Physiology, 2017)
Insects must undergo ecdysis for successful development and growth, and the ecdysis triggering hormone (ETH), released by the Inka cells, is a master hormone in this process. In this study, we determined the sequence of the ETH precursor and receptors in an agriculturally important pest insect, the oriental fruit fly Bactrocera dorsalis (Hendel). We identified two functionally distinct splice receptor isoforms: BdETH-R-A and BdETH-R-B, and when expressed in Chinese hamster ovary (CHO-WTA11) cells, they exhibited a high sensitivity to the two mature peptides BdETH1 and BdETH2. The BdETH transcript was detected in the tracheal tissue of the larvae. Inka cells were identified with immunohistochemical antibody staining against Drosophila melanogaster ETH1, and in situ hybridization with specific DNA probes. Selective RNA silencing of BdETH or BdETH-R-A, but not of BdETH-R-B, caused developmental failure at ecdysis. The dsRNA-treated larvae displayed tracheal defects and could not shed the old cuticle followed by death. Our results demonstrated that BdETH, via activation of BdETH-R-A but not ETH-R-B, plays an essential role in regulating the process of larva-larva ecdysis in B. dorsalis.